Front cover & preliminary pages (Journal of Irish Urban Studies, Vol.2 (No. 1), 2003 - (:unkn) unknown (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
Front cover & preliminary pages, Journal of Irish Urban Studies, Vol.2 (Issue 1), 2003
Keywords: Urban geography -- Ireland